KEBIJAKAN LUAR NEGERI AUSTRALIA DALAM MERESPON DOMINASI CHINA PADA KERANGKA INDO-PASIFIK TAHUN 2013 - 2018 - Hanum, Nabila; Olivia, Yessi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The focus of this paper explains the foreign policy of Australia regarding the domination and expansion of China in Indo-Pacific. China's rise which consists of economic and military revolution, partnership, investment, and trade, has remade the landscape of regional system and also created tensions for other countries. Australia notices that China’s economic power will have geopolitical implications that will affect its national interest in the future. That is why Australia must have a good strategy and foreign policy to counter China's influence while remains engaged and builds a strong partnership with China.This paper uses the perspective of Neorealism which focuses on the anarchy structure, distribution of power, security dilemma, and also the balance of power in the system. Using the balancing and engagement theory, this research aims to unveil Australia’s strategy and approach to China’s rise. The hypothesis examined using the level of analysis of the nations as it directly related to Australia's Foreign Policy White Paper 2017 that primarily focuses on Indo-Pacific opportunities for Australia. This research shows the Australian government has a strong commitment to create a peaceful and open Indo-Pacific region to coordinate its position by building and increasing cooperation and partnership with other countries around Indo-Pacific. So that they can achieve a balance of power in order to counter and moderate China's influence and border its growth in the vast and complex Indo-Pacific region, so that it is not overlapped with the interest of other countries. Meanwhile, Australia also tries to remain engaged with China by increasing the partnership and investment to preserves the strong and good relationship between both countries.  Keywords: Indo-Pacific, Foreign Policy White Paper, China Rise, Domination, Balancing and Engaging.